Undernutrition disrupts jejunal and ileal microbiota and epithelial tissue homeostasis in a pregnant sheep model - Weibin Wu; Muhammad Faheem Akhtar; Jiahong Geng; Huizhen Lu; Muhammad Ajwad Rahim; Jianbo Cheng; Xiaoling Ding; Shengyong Mao; Yanfeng Xue (Animal Nutrition)
Nutrition consistently affects microbe-host interactions in the gastrointestinal tract. This study aimed to unravel how undernutrition reshapes the microbial composition and the homeostasis of epithelium in the jejunum and ileum. Sixteen late-gestation Hu-sheep were randomly assigned to the control group (n = 8, 100% ad libitum feeding levels) or the undernutrition group (n = 8, which received 30% ad libitum feeding levels). After 15-d treatment, all ewes were slaughtered, and jejunal and ileal digesta and epithelium samples were collected for 16S rRNA gene sequencing and transcriptome sequencing, respectively. Results indicated that undernutrition decreased the jejunal and ileal tissue weights (P = 0.005 and P = 0.022) and the levels of volatile fatty acids (P = 0.019 and P = 0.007) and microbial protein levels (P = 0.019 and P = 0.031) in jejunal and ileal digesta. The relative abundance of acetate producing microbiota, including Clostridia UCG-014 norank, Ruminococcus, [Ruminococcus] gauvreauii, and Lachnospiraceae_Blautia, were significantly reduced (P < 0.05) in the jejunum and ileum. Undernutrition up-regulated (P < 0.05) the expression of genes involved in amino acid synthesis and fatty acid oxidation, but down-regulated (P < 0.05) the expression of genes associated with amino acid degradation, fatty acid synthesis, and extracellular structures in jejunal and ileal epithelium. In the jejunal epithelium, genes associated with extracellular matrix–receptor interactions, cell growth, and immune response were down-regulated (P < 0.05) upon undernutrition. Taken together, undernutrition changed the microbial community in the jejunum and ileum, which altered the fermentation mode and the production of volatile fatty acids and microbial protein. These affected the energy and protein system in the epithelium and reprogrammed substance metabolism and extracellular structures, which probably further influenced cell growth and immune response. These insights provide a foundation for completely clarifying the crosstalk between small intestinal microbiota and the host.